The incidence of severe urinary tract infection increases after hip fracture in the elderly: a nationwide cohort study - Lin, Yi-Ching (Sci Rep, 2021)
Although urinary tract infection (UTI) is a common perioperative complication among elderly patients with hip fracture, its incidence and effects are often underestimated. This study investigated the effects of severe UTI (S-UTI) on elderly patients with hip fracture and the risk factors for this condition. In this retrospective nationwide cohort study, we searched Taiwan’s National Health Insurance Research Database from 2000 to 2012 for data on patients aged ≥ 50 years with hip fracture who underwent open reduction and internal fixation or hemiarthroplasty for comparison with healthy controls (i.e. individuals without hip fracture). The study and comparison cohorts were matched for age, sex, and index year at a 1:4 ratio. The incidence and hazard ratios of age, sex, and multiple comorbidities associated with S-UTI were calculated using Cox proportional hazard regression models. Among the 5774 and 23,096 patients in the study and comparison cohorts, the overall incidence of S-UTI per 100 person-years was 8.5 and 5.3, respectively. The risk of S-UTI was cumulative over time and higher in the study cohort than in the comparison cohort, particularly in those who were older, were female, or had comorbidities of cerebrovascular accident or chronic renal failure.